Pengembangan Kompetensi Konselor Melalui Pelatihan Konseling Adiksi Berbasis Emotional Freedom Technique - Sugara, Gian Sugiana; Muhajirin, Muhammad; Rahimsyah, Anandha Putri (Kreativasi : Journal of Community Empowerment, 2025)
Addiction counseling training is a strategic effort to improve the professional competence of Guidance and Counseling (BK) teachers in dealing with increasingly complex addiction problems among students. This activity not only strengthens conceptual understanding of addictive behavior, but also equips teachers with practical skills to provide effective and evidence-based interventions. One of the approaches introduced in this training is the Emotional Freedom Technique (EFT), an energy-based psychological technique that has been proven to reduce stress, anxiety, and compulsive drives that often underlie addictive behavior. The results of the training showed that BK teachers gained significant improvements in their knowledge and intervention skills, and were able to apply EFT adaptively in counseling services in schools. These findings emphasize the importance of ongoing professional development that not only focuses on cognitive aspects, but also includes practical approaches that are relevant to the psychosocial needs of students. Thus, this training contributes directly to improving the quality of guidance and counseling services in schools.